ANALYSIS OF DEBTOR'S EFFORTS IN SETTLEMENT OR IMPLEMENTING CREDIT OBLIGATIONS DURING THE NON-NATURAL NATIONAL DISASTERS OF THE COVID-19 PANDEMIC - Barus, Artanta; Chandra, Tofik Yanuar; Sinaulan, Ramlani Lina (Transpublika Publisher, 2022)
Due to Covid-19 pandemic many debtors unable to fulfill their obligations to creditors in a credit agreement. Such conditions rising the opinion and/or use the Covid-19 Pandemic as an excuse for debtor not to fulfill their obligations to creditors in a credit agreement on the grounds of forced circumstances (overmacht). This study aims to find out the debtor's efforts in settlement or implementing credit obligations during the non-natural national disasters of the covid-19 pandemic. The type of research used is normative legal studies, which are conducted through a process of legislation and regulatory evaluation. In terms of technique, scientifically normative legal science disclosure methods are constrained by deductive logic criteria. This study employed normative legal research methods. This method investigates law from an internal juridical standpoint, examining legal norms, legal conceptions, legal principles, and legal doctrines. The technique taken in this research is a legal and conceptual one, with primary and secondary legal material sources. The technique for collecting legal materials is to assess all books relevant to the subject of the research, and then compile them in a quantifiable and systematic manner. The findings highlight that with the prevailing laws and regulations due to the Covid-19 Pandemic, business actors are given legal certainty for business loans made in this case debtors, both individual debtors and business entity debtors, so that the impact of credit risk caused by the Covid-19 pandemic can be overcome properly and does not cause a debate over credit conditions during the Covid-19 Pandemic.